Mc Cune Albright syndrome: gynecological perspective - Thangamani M.; P., Priyadharshini; Dharani E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The key features of McCune-Albright syndrome include sexual precocious puberty, polyostotic fibrous dysplasia and café au lait spots. It is associated with hyperfunction of multiple endocrine glands. Other endocrine dysfunctions often associated are growth hormone excess, hyperthyroidism, Cushing’s syndrome, hyperprolactinemia and phosphate wasting. We had a case of McCune-Albright syndrome with precocious puberty and irregular cycles and was managed. It is a rare cause of precocious puberty and should be kept in mind while dealing with such cases.